2016
DOI: 10.1039/c5py00797f
|View full text |Cite
|
Sign up to set email alerts
|

Micelles from self-assembled double-hydrophilic PHEMA-glycopolymer-diblock copolymers as multivalent scaffolds for lectin binding

Abstract: We introduce a novel double-hydrophilic hydroxyethylmethacrylate (HEMA) based diblock glycopolymer which self-assembles into homogeneous spherical micellar structures in water. The micellar structure renders surface-oriented N-acetylglucocosamine (GlcNAc) sugar moieties for strong multivalent glycan-mediated lectin binding. Structural analysis and lectin binding is performed by microscopy methods, dynamic light scattering (DLS) and two-focus fluorescence correlation spectroscopy (2fFCS), revealing a novel mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…22 On the other hand, glycomaterials also display interesting characteristics in many biological recognition events, such as cell-cell adhesion and development of new tissues, and thus have potential applications in targeted drug delivery, tissue engineering, and synthesis of biocompatible materials. 23,24 Micro-organisms exhibit preferential adhesion to specific substrates, and this characteristic is a plausible target in the design of new antimicrobial compounds. It was suggested that the phagocytic cells of certain nonopsonized Escherichia coli express type I fimbriae that recognize mannose.…”
mentioning
confidence: 99%
“…22 On the other hand, glycomaterials also display interesting characteristics in many biological recognition events, such as cell-cell adhesion and development of new tissues, and thus have potential applications in targeted drug delivery, tissue engineering, and synthesis of biocompatible materials. 23,24 Micro-organisms exhibit preferential adhesion to specific substrates, and this characteristic is a plausible target in the design of new antimicrobial compounds. It was suggested that the phagocytic cells of certain nonopsonized Escherichia coli express type I fimbriae that recognize mannose.…”
mentioning
confidence: 99%
“…At higher concentration between 5 and 20 wt% large particles were observed via optical microscopy. Micelles from self‐assembled DHBCs including a glycopolymer block were presented by Böker and co‐workers . A DHBC, namely, poly(2‐hydroxyethyl methacrylate)‐ b ‐poly(2‐O‐( N ‐acetyl‐β‐ d ‐glucosamine)ethyl methacrylate), was formed via ATRP.…”
Section: Double Hydrophilic Block Copolymer Systems For Self‐assemblymentioning
confidence: 99%
“…In such a way, various examples of DHBC self-assembled structures were described, e.g. vesicles, 21,22 micelles [23][24][25] or particles. [26][27][28] In addition, mesophases of DHBCs in water were observed at high concentrations.…”
Section: Introductionmentioning
confidence: 99%